Students' Live Experiences of Factors Affecting Academic Motivation: A Qualitative Study - marziye pirikamrani; hosein salimibejestani; kiumars farahbakhsh; abdolah motamedi (پژوهش در نظام‌های آموزشی, 2020)
The purpose of this study was to describe the living experiences of 12th grade students of academic motivation. The research method was qualitative and data collection tool was interview. The study population was 12th grade students. The sampling was purposeful so that until the new information was no longer available, the sampling would end, so the sample consisted of 19 students who participated in a semi-structured interview. The data obtained from the interviews were analyzed using the grounded theory method and the texts were analyzed by qualitative content analysis and the main categories of academic motivation were extracted. Thus, the factors affecting academic motivation were coded into three main categories, each with additional subcategories. The main categories obtained are: 1- Individual factors including sub-categories of goal-setting, energy, bright future, self-confidence, self-efficacy, success, interest and learning strategies; 2 family factors including parent support and encouragement; 3. Social factors including encouraging friends and peers, modeling who succeeded. In general, academic motivation is influenced by many factors such as the individual, family and community.